Self-Regulation in Informal Workplace Learning: Influence of Organizational Learning Culture and Job Characteristics - Kittel, Anne F. D.; Kunz, Rebecca A. C.; Seufert, Tina (Frontiers in Psychology, 2021)
The digital shift leads to increasing changes. Employees can deal with changes through informal learning that enables needs-based development. For successful informal learning, self-regulated learning (SRL) is crucial, i.e., to set goals, plan, apply strategies, monitor, and regulate learning for example by applying resource strategies. However, existing SRL models all refer to formal learning settings. Because informal learning differs from formal learning, this study investigates whether SRL models can be transferred from formal learning environments into informal work settings. More precisely, are all facets relevant, and what are there similar relational patterns? Because informal workplace learning occurs through interaction with the context, this study investigates the influence of context, i.e., organizational learning culture and job characteristics (autonomy, task identity, and feedback) on SRL. Structural equation modeling of N = 170 employees in various industries showed the relevance of the self-reported metacognitive strategies, planning, monitoring, and regulation; the resource strategies help-seeking and effort regulation; and deep processing strategy elaboration. However, there was no evidence for organization strategies. The learning strategies were associated with self-efficacy and mastery-approach goal orientation. Regarding context, results supported indirect effects over self-motivational beliefs of learning strategies. Organizational learning culture was connected with mastery-approach goal orientation, whereas job characteristics autonomy and feedback were related to self-efficacy, which were again related to SRL strategies. Therefore, context can empower employees not only to accomplish their tasks but to develop themselves by applying SRL strategies. The results are discussed, and practical implications are outlined.